Microsurgical dissection of facial nerve in parotidectomy: a discussion of techniques and long-term results - SAÇAK, BÜLENT (AME PUBL CO, 2017)
Background: Parotidectomy has well-documented post-operative complications. Dissection of the facial nerve branches can be challenging even under loupe magnification, and partial, or complete injury of the nerve branches can occur during surgery. To reduce this risk and the associated complications, we propose a number of microsurgical best practices, which can be performed during parotidectomy. Methods: A retrospective survey was conducted on 109 patients (45 males and 64 females, average age 46.2 years, range of 6 to 74 years) who underwent parotidectomy in two different institutions. Results: Our data showed no permanent injury to the facial nerve, and 17% of neuroapraxia that had resolved with time. Post-operative complications have occurred in 33 cases (30% rate). In the superficial parotidectomy cohort (78 patients), the number of complications was 17 (21%). In the total parotidectomy cohort (31 patients), the number of complications was 16 (51%). Conclusions: Based on our results, we believe that the use of microsurgical techniques during parotidectomy may represent a useful tool in improving accuracy and minimising local tissue trauma that can affect nerve recovery. This is particularly true in situations such as tumor recurrence, tissue fibrosis or in case of sizeable tumors around the facial nerve branches. We believe that the decreased risk of facial nerve postoperative symptoms outweigh the disadvantage of increased operative time of this procedure.
Keywords: Facial nerve; parotid; parotidectomy; parotid tumor; microsurgery; QUALITY-OF-LIFE; BENIGN DISEASE; SUPERFICIAL PAROTIDECTOMY; PLEOMORPHIC ADENOMA; GLAND SURGERY; COMPLICATIONS; EXPERIENCE; MORBIDITY; BRANCH